A Lost Opportunity? Omission of the Illusory Trust Doctrine from the Trusts Act 2019 - Probert, Thomas (Victoria University of Wellington Law Review, 2019)
This article considers the role of the illusory trust doctrine in New Zealand. It argues that the illusory trust doctrine should be incorporated into the Trusts Act 2019. Incorporating the illusory trust will enhance clarity in New Zealand's law of trusts by providing the courts with a conceptually coherent method to assess the permissible boundaries of the trust. This article explores the differing views of illusory trusts in the context of the Trusts Act and in light of policy concerns. The "no meaningful accountability" view of illusory trusts is identified as the best formulation of the doctrine for incorporation into the Trusts Act. Importantly, the no meaningful accountability view does not jeopardise discretionary family trusts, which have social and economic significance. The author goes further by drafting a tentative provision for incorporation in the Trusts Act. The provision is then applied to the nefarious Clayton v Clayton trust and a typical, discretionary family trust. This application demonstrates that the provision will only catch the most nefarious Clayton-type trusts, thus preserving discretionary family trusts.